Functionalization and exfoliation of bulk graphite into few-layer graphene sheets for improved heat dissipation / Ahmad Amiri - Ahmad , Amiri (2017)
It is evident that the studies on exfoliation of graphite into graphene for preparing stable colloidal samples have been a major subject of interest among researchers both in academia and industry. Thus, the present research had been directed towards understanding the mechanisms of exfoliation and covalent functionalization, and exploring of viable, scalable and efficient techniques to improve the stability of graphene sheets and ultimately paving routes for applying the concept into real engineering applications. Three major topics were pursued within the current research perspective. The first topic emphasizes on the exploration of facile and economical exfoliation methods for the scalable synthesis of few-layered graphene sheets. To this end, in situ liquid phase exfoliation and functionalization was employed. Surprisingly, the morphological and statistical studies showed that more than 90% of the flakes had less than two layers and about 84% of graphene sheets were single-layered in one of the procedures. Also, the BET analysis indicated that the SSA of different graphene sheets prepared in this study was up to 1559 m2/g. The second topic focuses on the benign and facile preparation of water-based highly stable functionalized graphene nanofluids and its role on enhancing the thermo-physical properties. Water-based highly porous single layer graphene (SGr), water-based crumpled few-layer graphene (HCFLG), and water-based functionalized graphene nanoplatelets dispersions were prepared. Further, the maximum sediments of less than 2% and 13 % were obtained for water-based HCFLG and waterbased SGr dispersions, respectively, which are quite impressive. Also, the addition of HCFLG and SGr into the basefluids produced noticeable increases in the thermal conductivity, up to 42.5% and 26%, respectively. Insignificant average drops of <1% in Cp were observed after addition of SGr or HCFLG into the water at the weight concentration of 0.001–0.01 wt%. Also, the density of the water-based HCFLG nanofluids, water-based SGr nanofluids, and water/ethylene glycol-based EG-GNP nanofluids at weight concentration of 0.01% decreases by 1.01 and 0.99%, 0.87 and 0.88%, and 0.01 and 0.1%, when the temperature increases from 20 to 50 °C, respectively. The final topic deals with the field testing of various colloidal dispersions with improved stability within energy transport system. A duct with a backward-facing step experimental set-up working in transition and turbulent modes and subjected to constant heat flux was established. As compared to the base fluid, the maximum enhancement in average heat transfer coefficient for transitional and turbulent flow regimes was 271% and 177% in the presence of water-based SGr nanofluid at 0.01 wt%, respectively. The amount of enhancement was 233.5% and 199% for water-based HCFLG nanofluids, respectively. Also, the average thermal performance of car radiator in the presence of water/EG-based ethylene glycol-treated GNP nanofluids increased by 99.9%, 102.2% and 115.3% for inlet temperature of 35, 45 and 55 °C, respectively. Other characteristics of the new coolants such as weak increase in the pressure drop and required pumping power (less than 2%), low friction factor, lack of corrosive agent, and appropriate performance index (PI> 1) are all highly favorable for introducing new fluids for wide industrial applications.